Polish Independent Press Review, no. 11 (1986) - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Topical reviews of Polish samizdat publications in English prepared by RFE staff members to be used by different national broadcasting units. PIPR was published from 1986 until November 1989 as a continuation of Polish Underground Extracts (PUE). The 10th Anniversary of KOR. The Beginnings of Open and Nonviolent Opposition / by Nika KrzeczunowiczThe "food riots" in the summer of 1976 resulted in brutal repression directed against the workers at the Ursus Tractor Factory and in the town of Radom, where there was rioting in several plants. A small group of volunteers set out to help the workers and their families and finally won over to their cause prominent intellectuals who banded together in the Workers' Defense Committee [Komitet Obrony Robotników (KOR)] in September 1976. Personal Engagement / by Nika KrzeczunowiczThe first rule of KOR was not to avoid personal involvement and even danger in helping others. This item gives several examples of such devotion and describes some of the more prominent members of KOR. How KOR Helped the Workers / by Anna PomianKOR operated in the "gray area" between what is permissible under Polish law and what contravenes it; this openness of KOR's activity led to the creation of the Intervention Bureau, which was set up to help workers, their families, and other victims of the regime's repression. It provided them with legal, medical, and financial aid. Help for political prisoners continues to be a feature of opposition activity today. KOR's Contacts with Other Bloc Countries / by Anna PomianRepresentatives of the KOR movement established contact with both Western and Eastern countries; meetings were held with Charter 77 from Czechoslovakia and the Hungarian opposition. In 1979 Zbigniew Romaszewski, a leading KOR member, visited Professor Andrei Sakharov in Moscow. Conclusion / by Nika Krzeczunowicz